Hacia una educación con equidad - Sandra Emma Carmona-Valdés (Universidad del Magdalena, 2015)
At the Fourth World Conference on Women held in Beijing in 1995, the Government of Mexico is internationally committed to ensuring women's access to equitable social opportunities, economic, political, labor, educational, cultural and health (UN Organization, 1995). The aim of this paper is to analyze gender policies implemented in Mexico in education with respect to the guidelines established in the Fourth World Conference on Women. The documentary research used ATLAS.ti to systematize information, each political will and positive action filed is a specific response to two main demands set out in the guidelines established in the Beijing Platform for Action (access and retention of women formal education and training in gender equity) and encompass the set of actions to achieve gender equality by the various agencies of the State. Against compromise ratified internationally for equal access to educational opportunities, and gender training from formal education have made significant progress; however, persistent inequalities require greater efforts to establish equitable opportunities for men and women that would achieve a more just and equitable society